Enhancing Religious Tourist Satisfaction: The Role of Service Quality and Facilities at Bubohu, Gorontalo - Perdana, Dian Adi; Abdul Rahim Hamzah; Hendri Ajihuda; Abdul Charis; Saerozi (Jurnal Ekologi, Masyarakat dan Sains, 2025)
Bubohu religious tourism is located in the coastal area of ??Bongo Village and is close to other tours, namely the Walima Emas Mosque and Dulanga Beach. This tour is close to hilly areas and the sea which is the main attraction. This halal tourism industry has an attraction for both domestic and foreign people, so that from time to time it continues to grow. This privately managed halal tourism continues to improve the quality of services and facilities to provide the best for visitors. This study aims to examine and analyze the effect of service quality and facilities on visitor satisfaction of religious tourism "bubohu". This research is a causality study with a quantitative approach. The population is all visitors to religious tourism "bubohu" in Gorontalo Province, while the sample is determined as many as 100 visitors by using random sampling. Data were collected using a questionnaire, then analyzed using multiple regression analysis. The results of the research show that the quality and service facilities, partially or jointly, have a significant effect on the satisfaction of visitors to the Bubohu religious tourism, with more than 50% of Gorontalo people feeling satisfaction when traveling or visiting the Bubohu religious tourism.